Red Cell Distribution Width After Subarachnoid Hemorrhage. Issue 4 (October 2018) - Fontana, Vito; Bond, Ottavia; Spadaro, Savino; Annoni, Filippo; Nobile, Leda; Badenes, Rafael; Volta, Carlo A.; Vincent, Jean-L.; Creteur, Jacques; Taccone, Fabio S.
Abstract : Background: High red cell distribution width (RDW) values have been associated with increased hospital mortality in critically ill patients, but few data are available for subarachnoid hemorrhage (SAH). Methods: We analyzed an institutional database of adult (>18 y) patients admitted to the Department of Intensive Care after nontraumatic SAH between January 2011 and May 2016. RDW (normal value, 10.9% to 13.4%) was obtained daily from admission for a maximum of 7 days, from routine blood analysis. We recorded the occurrence of delayed cerebral ischemia (DCI), and neurological outcome (assessed using the Glasgow Outcome Scale [GOS]) at 3 months. Results: A total of 270 patients were included (median age 54 y—121/270 male [45%]), of whom 96 (36%) developed DCI and 109 (40%) had an unfavorable neurological outcome (GOS, 1 to 3). The median RDW on admission was 13.8 [13.3 to 14.5]% and the highest value during the intensive care unit (ICU) stay 14.2 [13.6 to 14.8]%. The RDW was high (>13.4%) in 177 patients (66%) on admission and in 217 (80%) at any time during the ICU stay. Patients with a high RDW on admission were more likely to have an unfavorable neurological outcome. In multivariable regression analysis, older age, a high WFNS grade on admission, presence of DCI or intracranial hypertension, previous neurological disease, vasopressor therapy and a high RDW (OR, 1.1618 [95% CI, 1.213-2.158]; P =0.001) during the ICU stay were independent predictors of unfavorable neurological outcome. Conclusions: High RDW values were more likely to result in an unfavorable outcome after SAH. This information could help in the stratification of SAH patients already on ICU admission.